The Effect of Washing Treatments and Natural Adsorbent Application to the Quality of Fresh Cassava (Manihot utilissima) - Mardiyani, Siti Asmaniyah; Nasrudin, Anas (Universitas Islam Malang, 2024)
A research to know the influence of washing treatments and various natural adsorbent as storage media of fresh cassava has been done in Agriculture laboratory of the University of Islam Malang. The research was done using 2 factors (washing treatment and of natural adsorbents). The first factor consisted of 2 levels: no washing and washing treatment. The second factor consisted of 5 levels (without natural absorbent, river sand, charcoal husk, wood charcoal, and ashes). The storage was done for 2 weeks. The parameters observed were weight loss (%), moisture content (%), total soluble solid, total microbes, and sensory test (colour, aroma, and taste of the cassava). The result showed that quantitatively the cassava stored in the river sand without water treatment gave the best performance. It had the highest water content (33,40%) at the last observed (2 weeks storage). Respondents liked the cassavas which were stored in the river sand as adsorbent media. Further research using river sand l as the natural adsorbent in cassava storage should be done accurately to know the effect of the adsorbent to the nutrition change and economic value of the storage system.